2019
DOI: 10.1097/qai.0000000000002126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Virological Outcomes of TB/HIV Coinfected Patients Treated With Dolutegravir-Based HIV Antiretroviral Regimens: Programmatic Experience From Botswana

Abstract: Background: Dolutegravir (DTG) has recently been recommended as a preferred first-line regimen for the treatment of new and treatment experienced HIV infected patients. However, potential drug interactions between DTG and rifampicin remain a clinical and public health concern. Methods:We analyzed HIV and TB treatment outcomes of HIV-infected patients concomitantly receiving rifampicin-and DTG-based regimens under programmatic conditions in Botswana. The outcomes of interest were successful TB treatment and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 6 publications
1
23
0
2
Order By: Relevance
“… 3 A recent observational study from Botswana reported similar virologic outcomes in patients on rifampicin taking DTG 50 mg 12-hourly versus 50 mg daily. 9 The RADIANT-TB trial is being conducted in Cape Town and is enrolling patients on TB treatment and starting first-line ART who are being randomised to TDF/FTC/DTG 50 mg 12-hourly versus TDF/FTC/DTG 50 mg daily ( https://clinicaltrials.gov/ct2/show/NCT03851588 ). Until data from this trial are available, we recommend DTG be dosed at 50 mg 12-hourly in all patients on rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“… 3 A recent observational study from Botswana reported similar virologic outcomes in patients on rifampicin taking DTG 50 mg 12-hourly versus 50 mg daily. 9 The RADIANT-TB trial is being conducted in Cape Town and is enrolling patients on TB treatment and starting first-line ART who are being randomised to TDF/FTC/DTG 50 mg 12-hourly versus TDF/FTC/DTG 50 mg daily ( https://clinicaltrials.gov/ct2/show/NCT03851588 ). Until data from this trial are available, we recommend DTG be dosed at 50 mg 12-hourly in all patients on rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of TLE400 STR over TLD STR (current WHO-recommended preferred first-line ART) include noninferior virological and immunological efficacy [26], lower incidence of obesity [19,20,26], safety and efficacy in pregnancy [27], and no need for dose adjustment in cases of HIV/TB coinfection (doubling of DTG dose needed when used with rifampicin) [36]. In a study by Lamorde et al, switching PWH who were on various NNRTI-containing first-line ART regimens to DTG-containing first-line ART led to an increased incidence of new-onset hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of these limitations, our study has strengths resulting in significant contributions to the body of scientific evidence available to HIV programs in DRC. Our findings coupled with the emerging evidence show that patients with TB/HIV coinfection require special attention and treatment, including TB-HIV integrated care and specific first-line therapies (e.g., dolutegravir) to improve treatment outcomes [ 35 , 36 ]. Our study utilizes a robust sample size to allow stable estimates of the influence of TB/HIV coinfection on outcome variables, after controlling for several sociodemographic and clinical variables included in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 94%